Afrotizea gen. nov. from tropical Africa (Coleoptera: Chrysomelidae: Galerucinae). - Stapel, Heidi; Wagner, Thomas (Contributions to Entomology = Beiträge zur Entomologie, 2001)
Candezea mashuana Jacoby, 1895 (= Candezea annulicornis Jacoby, 1906; syn. nov.) is phylogenetically not closely related to Candezea Chapuis, 1879, Monolepta Chevrolat, 1837, or Afrocrania Hincks, 1949, and herein transferred to Afrotizea gen. nov. with is subsequently described and figured. Afrotizea mashuana (Jacoby, 1895) is type species by monotypy. Keywords Africa, Chrysomelidae, Galerucinae, taxonomy, new name, new genus. Nomenclatural Acts mashuana (Jacoby, 1895) (Afrotizea), comb. n. hitherto Candezea mashuana annulicornis Jacoby, 1906 (Candezea), syn. n. of Afrotizea mashuana (Jacoby, 1895) Afrotizea Stapel & Wagner, 2001 (Chrysomelidae), gen. n.